INTERNATIONAL AND NATIONAL RESEARCH METHODS ON REGIONAL TOURISM - Anvarova Muhsinakhon Otabek kizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This scientific article examines International and National Research Methods on Regional Tourism, focusing on their comparative features, methodological frameworks, and practical implications for sustainable tourism development. The study employs a mixed-methods approach that integrates both quantitative and qualitative research designs to analyze the effectiveness of different methodological models in regional tourism studies. Through literature review, statistical evaluation, and case study analysis, the research identifies the strengths and limitations of international and national approaches. The results indicate that international research methods provide valuable global comparability, while national methods offer deeper contextual understanding. The article concludes that a hybrid model — combining international analytical rigor with national contextual sensitivity — ensures more accurate, inclusive, and sustainable outcomes in regional tourism development. Recommendations are provided for improving data systems, promoting cross-border academic collaboration, and aligning research with sustainable development goals (SDGs).